PENINGKATAN PATENSI PEMASANGAN IV LINE PADA NEONATUS DENGAN PENGGUNAAN ELASTIC BANDAGE - Fitri Widayati; Yuni S. Arief; Retnayu Pradanie (Pediomaternal Nursing Journal, 2014)
Introduction: Patency installation of IV line is band resilience installation of good IV line of place location of insersion husk and also around installation location. Based on CDC ( Centers for Disease Control ) recommendation IV line replacement time is 72 hours ( 3 days ). In neonates, the replacement of the IV line often happened before the third day. In our hospital, RSPS, we try to keep the IV line by using the fication method with elastic bandage ( elastomoule haff ). Therefore, we need to analyze the usage of elastic bandage on IV line neonates.Method: In this research, we try configure about the usage of elastomoule with the frequency of IV line charging, change of the limb colour and the phlebitis case. We use analytic descritive method for this research. The population is all the babies in NICU who used IV line with elastic bandage. Used sample and fulfill criteria of inclusion counted 12 sampel. Technics of intake of sample the used is sampling purposive. Perception conducted by using observation sheet instrument later, then tabulation obtained data and analysed to use test of analyze frequency descriptive.Result: Of research data analysis, got by percentage of replacement of IV site less than 3 day equal to 16,7%, natural of change of husk (redness) equal to 16,7% and occurence of phlebitis degree of 1 equal to 16,7% .Discussion: Thereby can be concluded that usage of elastic bandage have an effect on to patency installation of IV line at neonatus. Result of this research can be made by consideration in giving health service to attached by a baby with IV line installation therapy